Faktor-Faktor yang Mempengaruhi Minat Kunjungan Kembali Wisatawan ke Kawasan Kayutangan Heritage Kota Malang - Sari, Yuyun Desta; Muta’ali, Lutfi (JURNAL NASIONAL PARIWISATA, 2025)
The Kayutangan Heritage Area is one of the areas with cultural, historical, and architectural heritage in Malang City that has the potential to attract tourists. However, as time went by, the Kayutangan area began to fade and become less attractive due to both physically and non-physically. After the realignment, this area returned to life as an economic center and historical and cultural tourism. This research aims to identify factors that influence tourists' interest in returning to the Kayutangan Heritage Area. The sampling technique was accidental sampling. The data collection technique used in this research was a field survey with a questionnaire. The analysis was carried out using multiple linear regression using IBM-SPSS Statistics 26. The research results showed that the variables of attraction, accessibility, and amenities simultaneously had a significant effect on tourists' intention to revisit. Partially, the attractiveness and accessibility variables have a significant effect on tourists' interest in returning to visit, but the amenities variable does not have a significant effect on tourists' interest in returning to visit.